Reimagining Modern Education: Contributions from Modern Japanese Philosophy and Practice?. (March 2020) - Komatsu, Hikaru; Rappleye, Jeremy
Purpose: Amidst ongoing attempts to think beyond Western frameworks for education, there is a tendency to overlook Japan, perhaps because it appears highly modern. This is striking given that some prominent strands of Japanese philosophy have formulated an explicit and exacting challenge to the core onto-epistemic premises of modern Western thought. It is also surprising because Japanese educational practices have resulted in some of the highest achievement outcomes—both cognitive and noncognitive—found anywhere in the world and inculcate a worldview that is distinct. Design/Approach/Methods: Herein, we thus attempt to make visible the potential contribution of modern Japanese philosophy by outlining some of the core ideas, then turn to sketch resonances with and responses to other projects outlined in this Special Issue. Our approach is elucidation through relational comparison. Findings: Through this process, we suggest that the notion of self-negation as a mode of learning may be helpful in explaining why—at the empirical level—the outlook of Japanese students, and perhaps other East Asian students, diverge markedly from their Western peers. Yet we also find that an attempt, such as ours, to link divergent onto-epistemic thought to alternative empirical hypotheses quickly gives rise to various doubts and discomforts, even among otherwise sympathetic scholars. Originality/Value: In directly responding to these doubts, one original contribution of our piece is to show just how difficult it may ultimately be to divest from the symbolic foundations already laid by Western liberalism: Even if divergent thought can be imagined and different cultural narratives explored, dominant readings of empirical "realities" continue to be entrapped in the logic laid by Western liberalism.